Monitoring digoxin therapy: III. How useful are the nomograms? - Aronson, J (1978)
1. A previously described set of guidelines for digoxin therapy has been evaluated in twenty-four patients. 2. Six different published methods (nomograms and equations) for predicting digoxin requirements have been studied to determine their clinical usefulness in the context of the twenty-four patients. 3. The limitations of the nomograms and equations are discussed.